Hair glucocorticoid concentration, self-perceived stress and their associations with cardiometabolic risk markers in Swedish adolescents. (December 2022) - Chen, Yun; Petzold, Max; Rüetschi, Ulrika; Dahlstrand, Johan; Löfstedt, Petra; Corell, Maria; Friberg, Peter
Abstract: Background: While hair cortisol is proposed as a biomarker for chronic stress and a possible mediator linking chronic stress and cardiovascular risk in adults, studies in adolescents are scarce. We explored the associations between self-perceived stress, hair cortisol (HairF) and cortisone (HairE), and cardiometabolic risk markers in adolescents. Further, we examined whether association between self-perceived stress and HairF may depend on the use of the coping strategies "shift-persist". Methods: Participants were 7th grade pupils recruited to the STudy of Adolescence Resilience and Stress (STARS) and data from the baseline examinations were used. Adolescents (n = 1553, 26 % boys, Mage =13.6, SD = 0.4) completed questionnaires assessing perceived stress and coping strategies "shift-persist", provided hair sample, and examined for cardiometabolic risk factors including waist circumference (WC), body mass index (BMI) z-score, blood pressure, and white blood cell counts (WBC). HairF and HairE were analysed using liquid chromatography with tandem mass spectrometry. We conducted descriptive analyses (Student's t-test, Wilcoxon Signed Ranks test, Chi-square test) and linear regression analyses. Results: Perceived stress was not associated with HairF, neither had the use of coping strategies "shift-persist" any influence on this association. Both HairF and HairE were positively associated with BMI z-score (beta coefficients (β): 0.178 (p < 0.001) and 0.119 (p < 0.001) for boys; 0.123 (p < 0.001) and 0.089 (p < 0.01) for girls) and WC (β: 0.089 (p > 0.05) and 0.098 (p < 0.05) for boys; 0.103 (p < 0.01) and 0.076 (p < 0.05) for girls). Perceived stress was also positively associated with BMI z-score and WC. Perceived stress, but not HairF, remained associated with WC in boys (β = 0.200, p < 0.001) in the models with HairF and perceived stress presented simultaneously. Modest association between HairE and WBC was found in boys (β = 0.149, p < 0.01). Conclusions: The study supports the association between chronic stress and overweight/obesity in adolescents. Hair cortisol and self-perceived stress capture different aspects of how chronic stress is related to overweight/obesity in adolescents. Highlights: Hair glucocorticoids are associated with higher BMI and waist circumference in adolescents. Hair cortisol & perceived stress capture different aspects of how chronic stress is related to higher BMI & WC. Perceived stress did not reflect chronic activation of the HPA, neither had coping strategies influence on the association.